A reliable in vitro approach to assess the stability of acetabular implants using digital image correlation. (12th June 2019) - Morosato, F.; Traina, F.; Cristofolini, L.
Abstract: The main cause of failure of the hip acetabular component is aseptic loosening. Preclinical test methods currently used to assess the stability of hip acetabular implants rely on crude simplifications. Normally, either one component of motion or bone strains are measured. We developed a test method to measure implant 3D translations and rotations and bone strains using digital image correlation. Hemipelvises were aligned and potted to allow consistent testing. A force was applied in the direction of the load peak during level walking. The force was applied in 100‐cycle packages, each load package being 20% larger than the previous one. A digital image correlation system allowed measuring the cup‐bone relative 3D displacements (permanent migrations and inducible micromotions) and the strain distribution in the periacetabular bone. To assess the test repeatability, the protocol was applied to six composite hemipelvises implanted with very stable cups. To assess the suitability of the method to detect mobilisation, six loose implants were tested. The method was repeatable: the interspecimen variability was 16 μm for the bone/cup relative translations, 0.04° for the rotations. The method was capable of tracking extremely loose implants (translations up to 4.5 mm; rotations up to 30°). The strain distribution in the bone was measured, showing the areas of highest strain. We have shown that it is possible to measure the 3D relative translations and rotations of an acetabular cup inside the pelvis and simultaneously to measure the full‐field strain distribution in the bone surface. This will allow better preclinical testing of the stability of acetabular implants.